Ultrasound Measurement and Kidney Development: a Mini-Review for Nephrologists - Issa Al Salmi; Mahmood Al Hajriy; Suad Hannawi (Saudi Journal of Kidney Diseases and Transplantation, 2021)
Ultrasound (US) is a noninvasive, simple and safe imaging investigation that can be done as many times as needed. Therefore, it is the primary imaging modality for evaluating kidneys. We carried out a literature review of information about ultrasonography for clinicians, especially nephrologists. US utilization from prenatal time till adult life with various measurements including, length, width, depth, and volume was searched during 2019. US identifies 90% of fetal kidneys by 20 weeks of gestational age. Kidney weight and volume at birth are approximately only 10% of the mature kidney. Kidney growth is most rapid during the first few weeks of life, with the kidney length increasing by as much as 15–20% in full-term neonates. There is a good correlation between relative function shown by scintigraphy and relative volume estimated from sonography. The most accurate measurement of kidney size is provided by kidney volume, which is correlated with subject’s height, weight, and total body area. Kidney length is the most easily reproduced. Kidney volume is a better approximation of size than length because of the shape of the kidney varies considerably, but it is technically more demanding and needs four measurements in two different planes. It has been shown that in normal adult kidneys, the sonography measurements of kidney length differ by values of between about 1 cm and 1.85 cm in 95% of the cases, irrespective of whether the measurements are performed by the same or by different sonographers. Measuring the renal parenchyma with US is a novel method to assess fetal kidney development and predict future renal function.